2021
DOI: 10.1002/ajhb.23621
|View full text |Cite
|
Sign up to set email alerts
|

Testing the buffering hypothesis: Breastfeeding problems, cessation, and social support in the UK

Abstract: Objectives Physical breastfeeding problems can lead women to terminate breastfeeding earlier than planned. In high‐income countries such as the UK, breastfeeding problems have been attributed to the cultural and individual “inexperience” of breastfeeding, ultimately leading to lower breastfeeding rates. Yet, cross‐cultural evidence suggests breastfeeding problems still occur in contexts where breastfeeding is common, prolonged, and seen publicly. This suggests breastfeeding problems are not unusual and do not … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…While at first glance it may be surprising that participants who reported their health visitors to be emotionally supportive but informationally unhelpful had longer lactation durations than those who reported both informational and emotional supported positively, this may reflect a lack of need of informational support among these participants [5,50]. Earlier work with this sample has found that support clusters [48], suggesting participants with supportive health visitors were also likely to have ready access to other supporters who may duplicate information, dampening the perceived utility of their advice [51,52].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…While at first glance it may be surprising that participants who reported their health visitors to be emotionally supportive but informationally unhelpful had longer lactation durations than those who reported both informational and emotional supported positively, this may reflect a lack of need of informational support among these participants [5,50]. Earlier work with this sample has found that support clusters [48], suggesting participants with supportive health visitors were also likely to have ready access to other supporters who may duplicate information, dampening the perceived utility of their advice [51,52].…”
Section: Discussionmentioning
confidence: 96%
“…Informational support may also only be considered helpful if it solves a specific problem; parents without problems requiring assistance may give lower helpfulness ratings due to the nature of their experience, rather than the content or provision of support received. Since breastfeeding problems predict cessation [5], it may be that participants reporting health visitors as 'emotionally supportive and informationally not helpful' experienced fewer problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations